Quality and educational content of Douyin and TikTok short videos on early screening of rectal cancer - Lian‐Shuo Li; Xiao‐Juan Luo; Xin‐Peng Shu; Zi‐Wei Li; Fei Liu; Xu‐Rui Liu; Yue Tong; Quan Lv; Xiao‐Yu Liu; Wei Zhang; Dong Peng (JGH Open, 2023)
Abstract Background and Aim The aim of this study was to assess the quality and content of videos on Douyin and TikTok for their educational role on early screening of rectal cancer (RC). Methods We conducted a search for videos related to RC on the Douyin and TikTok applications on 20 April 2023. The search was conducted in Chinese on Douyin and in English and Japanese on TikTok. A sample of the first 100 videos recommended by the software was selected for each language group. The content of the videos was evaluated using a content scorecard, while the quality of the videos was assessed using DISCERN. Subsequently, we conducted two partial correlations: one between the DISCERN score and the number of likes, and another between the video content score and the number of likes. Results This study encompassed a total of 89 Chinese, 54 English, and 51 Japanese videos. After selection, 78 Chinese, 38 English, and 25 Japanese videos were identified to contain content related to early screening for RC, prompting further quality assessment. Notably, videos in the Chinese language showed the highest DISCERN score (P < 0.05). In terms of partial correlation analysis, it was observed that both the content score and DISCERN score did not show a significant correlation with the number of likes (P > 0.05). Conclusion In terms of quality score and content score, the Chinese videos on Douyin show superiority over the English and Japanese videos on TikTok. However, there is potential for improving the overall appeal of the Chinese videos.